Muslim exegeses perspective on creation of the first woman: a brief discussion - Ramli, M.A. (IDOSI Publications, 2013)
This article attempts to examine Muslim-exegeses discussion regarding first woman creation. In doing so, the view of classical Muslim-exegeses in this issue are compared with contemporary Muslim-exegeses’. Basically, this issue raised from the interpretation of nafs wahidah (single person) that derived from Quran, al-Nisa’ (4): 1. According to majority of classical Muslim-exegeses, that phrase refers to the creation of first woman (Eve) form Adam’s rib. This view has strongly supported by hadith which literally and directly endorsed the creation of first woman. While the second view, tend to asserted that the hadith can’t be interpreted in its literal meaning, but they choose to interpret it metaphorically. The third view, refuse the first opinion and they argue that it is based on patriarchy framework which has cause the degradation of women’s position in Muslim society. Hence, the finding shows that the second view is more feasible and parallel with Shariah teaching that promotes equality of human being especially in creation of man and woman. There’s no superior above inferior except who is most pious and righteous (taqwa).